Early Selection in Gag by Protective HLA Alleles Contributes to Reduced HIV-1 Replication Capacity That May Be Largely Compensated for in Chronic Infection - Brockman, Mark A; Brumme, Zabrina L; Brumme, Chanson J; Miura, Toshiyuki; Sela, Jennifer; Rosato, Pamela C; Kadie, Carl; Carlson, Jonathan M.; Markle, Tristan J; Streeck, Hendrik; Kelleher, Anthony D; Markowitz, Martin; et al. (Journal of Virology, 2010)
Mutations that allow escape from CD8 T-cell responses are common in HIV-1 and may attenuate pathogenesis by reducing viral fitness. While this has been demonstrated for individual cases, a systematic investigation of the consequence of HLA class I-mediated selection on HIV-1 in vitro replication capacity (RC) has not been undertaken. We examined this question by generating recombinant viruses expressing plasma HIV-1 RNA-derived Gag-Protease sequences from 66 acute/early and 803 chronic untreated subtype B-infected individuals in an NL4-3 background and measuring their RCs using a green fluorescent protein (GFP) reporter CD4 T-cell assay. In acute/early infection, viruses derived from individuals expressing the protective alleles HLA-B*57, -B*5801, and/or -B*13 displayed significantly lower RCs than did viruses from individuals lacking these alleles (P < 0.05). Furthermore, acute/early RC inversely correlated with the presence of HLA-B-associated Gag polymorphisms (R = −0.27; P = 0.03), suggesting a cumulative effect of primary escape mutations on fitness during the first months of infection. At the chronic stage of infection, no strong correlations were observed between RC and protective HLA-B alleles or with the presence of HLA-B-associated polymorphisms restricted by protective alleles despite increased statistical power to detect these associations. However, RC correlated positively with the presence of known compensatory mutations in chronic viruses from B*57-expressing individuals harboring the Gag T242N mutation (n = 50; R = 0.36; P = 0.01), suggesting that the rescue of fitness defects occurred through mutations at secondary sites. Additional mutations in Gag that may modulate the impact of the T242N mutation on RC were identified. A modest inverse correlation was observed between RC and CD4 cell count in chronic infection (R = −0.17; P < 0.0001), suggesting that Gag-Protease RC could increase over the disease course. Notably, this association was stronger for individuals who expressed B*57, B*58, or B*13 (R = −0.27; P = 0.004). Taken together, these data indicate that certain protective HLA alleles contribute to early defects in HIV-1 fitness through the selection of detrimental mutations in Gag; however, these effects wane as compensatory mutations accumulate in chronic infection. The long-term control of HIV-1 in some persons who express protective alleles suggests that early fitness hits may provide lasting benefits.